2006
DOI: 10.1002/ijc.22239
|View full text |Cite
|
Sign up to set email alerts
|

Incidence patterns of soft tissue sarcomas, regardless of primary site, in the surveillance, epidemiology and end results program, 1978–2001: An analysis of 26,758 cases

Abstract: Soft tissue sarcomas (STS) are a heterogeneous group of uncommon tumors that show a broad range of differentiation that may reflect etiologic distinction. Routine tabulations of STS are not morphology-specific. Further, the lack of inclusion of sarcomas arising in all organs in most standard evaluations underestimates the true rates. We analyzed the 1978-2001 Surveillance, Epidemiology and End Results program incidence rates of STS regardless of primary site, except bones and joints, using the 2002 criteria of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
391
11
15

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 561 publications
(444 citation statements)
references
References 47 publications
27
391
11
15
Order By: Relevance
“…Common tumor sites in different age groups were also similar to other population‐based studies 2, 4.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Common tumor sites in different age groups were also similar to other population‐based studies 2, 4.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, few other European studies, studies from the United Kingdom and the United States report a higher incidence of STS in males 15, for example, Toro et al. (U.S.A.) 2 and a regional study based in France and Italy 17. Hence, due to inconsistencies in results from various studies, clear gender predilection of STS cannot be obtained.…”
Section: Discussionmentioning
confidence: 98%
“…Higher incidence of STS in females, as found in Austria, is reported for Switzerland too [5]. In the United States, the two studies of Ross et al [6] and Toro et al [7] present different male-to-female ratios, even though both studies have comprised their dataset from the SEER program. In our study we found its slightly male predominance.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine sarcoma accounts for3-5% of all uterine malignancies (1) . This tumor has been considered as highly aggressive, showing a poor prognosis (2) .…”
Section: Introductionmentioning
confidence: 99%